2016
DOI: 10.1016/j.jcma.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Sox2, a stemness gene, regulates tumor-initiating and drug-resistant properties in CD133-positive glioblastoma stem cells

Abstract: SOX2 plays a crucial role in regulating tumorigenicity in CD133(+) GBM cells. Our results not only revealed the genetic plasticity contributing to drug resistance and stemness but also demonstrated the dominant role of SOX2 in maintenance of GBM CSCs, which may provide a novel therapeutic target to overcome the conundrum of poor survival of brain cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…SOX genes have been demonstrated to be associated with the differentiation and proliferation of cells (30), and have oncogene functions (31,32). It is reported that SOX10 and SOX1 are tumor-associated antigens of melanoma and small cell lung cancer cells, respectively (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…SOX genes have been demonstrated to be associated with the differentiation and proliferation of cells (30), and have oncogene functions (31,32). It is reported that SOX10 and SOX1 are tumor-associated antigens of melanoma and small cell lung cancer cells, respectively (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…These two types of glioblastoma CSCs although possess distinct features of growth and differentiation, both of them were able to induce tumor formation at a comparable level in nude mice (Beier et al, 2007). Between these two types, SOX2 was the most up-regulated stemness gene in the CD133 + glioblastoma cells and controlled tumorigenesis of this disease (Song et al, 2016). Knockdown of SOX2 hindered CD133 + -mediated tumor formation abilities in vivo.…”
Section: Cd133 In Cancer Initiationmentioning
confidence: 99%
“…More and more scholars have accepted the theory that tumors originate from CSCs. In addition to the above characteristics, CSCs also express several relatively specific biomarkers, such as CD133 [5], CD44 [6], NaNOG [7], and SOX2 [8], and overexpress anti-apoptotic genes, oncogenes, and other malignant biological markers, including telomerase and its hTERT subunit [9], BcL-2 [10], and survivin [11]. CSCs, tumor-like stem cells, or side population cells have been isolated from a variety of malignant tumors, including NPC [12,13].…”
Section: Introductionmentioning
confidence: 99%